Correlates of perceived social unacceptability of vaping among regular e-cigarette users: a cross-sectional study of a sample of Middle Eastern countries - AlMuraikhi, Hissa Mohamed; Chokor, Fatima Al Zahraa; Al-Hamdani, Mohammed (Frontiers in Public Health, 2025)
AimTo examine the association between the social unacceptability of vaping and the main correlate, country of residence, as well as other sociodemographic variables in three Middle Eastern countries.MethodsA cross-sectional online survey study of a convenience sample of regular vapers in Middle Eastern countries was recruited. Recruitment took place through paid advertisements on social media, regular e-cigarette users, completed an online survey. Vapers responded to socio-demographic and social unacceptability questions. Ordinal logistic regression was used for analysis.ResultsN= 428 vapers completed the survey. Male vapers and vapers who currently smoke had lower odds for social unacceptability perceptions relative to females and never smoker counterparts. Vapers in Qatar, experiencing pressure to vape from friends, encountering negative effects, and mod and e-cigarette use was associated with higher odds of social unacceptability perceptions relative to vapers in Egypt, not experiencing pressure from friends, not encountering negative effects, and pod use, respectively.ConclusionRelative to vapers in Egypt, those in Qatar reported higher social unacceptability levels, likely due to restrictive legislations, and calls for similar restrictions in Egypt. More awareness is needed to increase social unacceptability among vapers who are males and current smokers. Highlighting potential negative effects from vaping in education campaigns and regulatory restrictions on pod design (compact, sleek, and concealable features) may help increase the social unacceptability of vaping.